VOCATIONAL EDUCATION: ASSESSMENT, CLASSIFICATION AND THE REALM OF RESEARCH DEVELOPMENTS - Widianingsih, I.; Purwaamijaya, I. M.; Dwiyanti, V. (INVOTEC, 2018)
Education is one of the most important things to prepare for the competitive human resources in achieving success in the era of globalization. The main source of the success of the national development of a country is the development of human resources. Vocational education is expected to be one form of education that is able to develop human resources. Vocational education is an education that prepares students to work in a particular field.This article aims to examine the aspect and sphere of research related to vocational education. The method used is the study of literature relating to research on vocational education as well as an analysis of several publications. The results show that there is a wide range of topics related to vocational training, ranging from models of learning, instructional media, graduate competence, motivation, teacher performance, the role of industry to the development of vocational education, teaching materials of vocational education, information systems education, curriculum development of vocational education, policy government and stakeholders for the development of vocational education.